Critical analysis on digital marketing strategy of multipurpose financial society project management to identify gaps and recommended solution. - Jahan, Humayara Rownak (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.